Triheptanoin versus trioctanoin for long‐chain fatty acid oxidation disorders: a double blinded, randomized controlled trial. Issue 6 (4th September 2017) - Gillingham, Melanie B.; Heitner, Stephen B.; Martin, Julie; Rose, Sarah; Goldstein, Amy; El‐Gharbawy, Areeg Hassan; Deward, Stephanie; Lasarev, Michael R.; Pollaro, Jim; DeLany, James P.; Burchill, Luke J.; Goodpaster, Bret; et al.
Abstract: Background: Observational reports suggest that supplementation that increases citric acid cycle intermediates via anaplerosis may have therapeutic advantages over traditional medium‐chain triglyceride (MCT) treatment of long‐chain fatty acid oxidation disorders (LC‐FAODs) but controlled trials have not been reported. The goal of our study was to compare the effects of triheptanoin (C7), an anaplerotic seven‐carbon fatty acid triglyceride, to trioctanoin (C8), an eight‐carbon fatty acid triglyceride, in patients with LC‐FAODs. Methods: A double blinded, randomized controlled trial of 32 subjects with LC‐FAODs (carnitine palmitoyltransferase‐2, very long‐chain acylCoA dehydrogenase, trifunctional protein or long‐chain 3‐hydroxy acylCoA dehydrogenase deficiencies) who were randomly assigned a diet containing 20% of their total daily energy from either C7 or C8 for 4 months was conducted. Primary outcomes included changes in total energy expenditure (TEE), cardiac function by echocardiogram, exercise tolerance, and phosphocreatine recovery following acute exercise. Secondary outcomes included body composition, blood biomarkers, and adverse events, including incidence of rhabdomyolysis. Results: Patients in the C7 group increased left ventricular (LV) ejection fraction by 7.4% ( p = 0.046) while experiencing a 20% ( p = 0.041) decrease in LV wall mass on their resting echocardiogram. They also required a lower heart rate for the same amount of work during a moderate‐intensity exercise stress test when compared to patients taking C8. There was no difference in TEE, phosphocreatine recovery, body composition, incidence of rhabdomyolysis, or any secondary outcome measures between the groups. Conclusions: C7 improved LV ejection fraction and reduced LV mass at rest, as well as lowering heart rate during exercise among patients with LC‐FAODs. Clinical Trial Registration:Clinicaltrials.gov NCT01379625.